Strategies to improve PrEP uptake among West African men who have sex with men: a multi-country qualitative study - Reyniers, Thijs; Babo, Stéphane Alain Yoro; Ouedraogo, Mamadou; Kanta, Ibrahima; Ekon Agbégnigan, Laurette; Rojas, Daniela; Eubanks, August; Anoma, Camille; Dah, Ter Tiero Elias; Mensah, Ephrem; Dembélé Keita, Bintou; Spire, Bruno; et al. (Frontiers in Public Health, 2023)
West African men who have sex with men (MSM) remain at substantial risk of acquiring HIV. Pre-Exposure Prophylaxis (PrEP) can be an effective game-changer to reduce the number of HIV infections in these MSM communities. To optimise the roll-out of PrEP, we need to better understand how we can increase its uptake. The objective of this study was to explore the perceptions of West African MSM towards PrEP and their proposed strategies to overcome barriers to PrEP uptake within their communities. Between April 2019 and November 2021, we conducted 12 focus group discussions with 97 MSM not taking PrEP, and 64 semi-structured interviews with MSM taking PrEP, in Burkina Faso, Côte d’Ivoire, Mali and Togo. Data collection and analysis were guided and conducted by local research teams, enabling a community-based participatory approach. A coordinating researcher collaborated with these local teams to analyse the data guided by a grounded theory approach. The results show that participants were generally positive towards PrEP and that MSM communities have become more aware of PrEP over the course of the study. We identified three main strategies for increasing PrEP uptake. Firstly, participants proposed to raise awareness and improve knowledge of HIV, as they considered the self-perceived risk of MSM in their communities to be low. Secondly, because of existing misconceptions and false information, participants proposed to improve the dissemination of PrEP so as to allow for informed choices, e.g. via peers or PrEP users themselves. Thirdly, as oral PrEP also entailed a risk of being associated with HIV or homosexuality, strategies to avoid stigmatisation (e.g. hiding of pills) were deemed important. These findings indicate that roll-out of oral PrEP and future other PrEP modalities should be accompanied by raising awareness and improving knowledge on HIV, and wide dissemination of information that focuses on the health-promoting aspect of these tools. Tailored delivery and long-acting PrEP modalities will be important to avoid potential stigmatisation. Sustained efforts to prevent discrimination and stigmatisation based on HIV status or sexual orientation continue to be highly important strategies to address the HIV epidemic in West Africa.